Collective atomic scattering and motional effects in a dense coherent medium - S. L. Bromley (Nature Portfolio, 2016)
Light scattering from a dense coherent medium is determined by the interplay of dispersive and radiative dipole–dipole interactions. Here, the authors control the motional effects that obscure the coherence of scattered light and study collective emission in a driven gas of cold strontium-88 atoms.